1997
DOI: 10.1038/sj.leu.2400707
|View full text |Cite
|
Sign up to set email alerts
|

The genetics of familial leukemia

Abstract: mechanisms operating in the common, sporadic cases. AnticiKeywords: leukemia; familial; anticipation pation occurs in Huntington disease, myotonic dystrophy, and other inherited neurodegenerative illness where it results from the expansion of unstable trinucleotide repeat sequences. IntroductionSince this remains as the only molecularly defined instrument for anticipation, I weigh the possibility that an analogous situ-A family history of leukemia in a first degree relative increases ation holds for leukemia g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(67 citation statements)
references
References 24 publications
5
62
0
Order By: Relevance
“…20 An analysis of seven published families reported that age at diagnosis of CLL is lower for affected offspring than for the affected parental generation. 21,22 The decline in age at diagnosis was 21 years (s.e. = 4.1 years) (P = 0.001).…”
Section: Introductionmentioning
confidence: 99%
“…20 An analysis of seven published families reported that age at diagnosis of CLL is lower for affected offspring than for the affected parental generation. 21,22 The decline in age at diagnosis was 21 years (s.e. = 4.1 years) (P = 0.001).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence in support of the multistep pathogenesis of AML includes: (1) clonal remission from AML; 43 (2) preleukemic syndromes, such as MDS, which progress to AML with associated acquisition of karyotype abnormalities; 44 and (3) rare families with an inherited predisposition to develop AML. 3,45 By establishing linkage to chromosome 21q22. SSCP analysis of IFNAR1.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to ionizing radiation also increases the incidence of AML as observed in the surviving population of Japan after atomic bombing [14]. There are also documented cases in which AML was developed by multiple members of a family exceeding the predictions of random chance events suggesting that there might also be a hereditary basis of the disease [15,16]. In part because of these differences, this malignancy is grouped under four categories according to WHO classification [17]: AML with recurrent genetic abnormalities, AML with multilineage dysplasia, therapy related AML; and myelodysplastic syndrome (MDS), and lastly, AML cases that are not suitable for classification in the previously groups.…”
Section: Types and Progression Pathways Of Leukemiamentioning
confidence: 99%